2019
DOI: 10.1590/1089-6891v20e-50220
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização Da Silagem De Grão De Milho Reidratado Associado Ao Resíduo De Tilápia

Abstract: 1Universidade José do Rosário Vellano -UNIFENAS, Alfenas, MG, Brasil. *Autor para correspondência -adauton.rezende@unifenas.br ResumoObjetivou-se avaliar as características bromatológicas, microbiológicas e perdas fermentativas da silagem de grão de milho reidratado com água ou soro de leite associado a diferentes níveis de inclusão do resíduo de tilápia. Utilizou-se um delineamento inteiramente casualizado em esquema fatorial 5x2 (cinco níveis de inclusão do resíduo de tilápia: 0; 12,5; 25; 37,5 e 50% em subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Although GL increased 120 days after ensiling, the results observed in the current study are similar to those of corn grain silages rehydrated with water, as observed by Ávila et al . (2019), who found values of 6.3% for GL. However, these authors evaluated only one opening time (90 days after ensiling the material).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although GL increased 120 days after ensiling, the results observed in the current study are similar to those of corn grain silages rehydrated with water, as observed by Ávila et al . (2019), who found values of 6.3% for GL. However, these authors evaluated only one opening time (90 days after ensiling the material).…”
Section: Discussionmentioning
confidence: 97%
“…(2011) during the corn grain ensiling process, proteolysis occurs, which results in the degradation of the protein matrix that surrounds the starch granules, explaining the increase in rumen degradability. Therefore, the use of cactus pear as a corn grain moistening additive, intensifies the grain fermentative process when compared to the results found in the literature for water-rehydrated corn grain silage (Arcari et al ., 2016; Carvalho et al ., 2017; Da Silva et al ., 2018 a , 2018 b , 2019; Ávila et al ., 2019). In addition, the corn grain silage rehydrated with cactus pear presents increased degradability in the first 30 days of the fermentative process, which is important because it allows silos to be opened and the silage to be used earlier when compared to water-rehydrated corn silage.…”
Section: Discussionmentioning
confidence: 99%
“…A exemplo de silagem de grão de milho reidratado, onde a compra do milho em grande escala e com preço competitivo atrai os produtores, o mesmo vale para a ração completa. Contudo, na silagem de TMR, todos os ingredientes podem ser comprados de forma estratégica na safra para serem fornecidos aos animais na entressafra, sendo armazenados como silagem de TMR durante todo esse período, sem a necessidade de um silo graneleiro, que é uma estrutura dispendiosa (DE ÁVILA et al, 2019).…”
Section: Vantagens Da Ensilagem De Ração Em Mistura Totalunclassified
“…A facilitação ao acesso a maquinários sofisticados possibilita a confecção de grandes quantidades de ração em mistura total, e também o acondicionamento do material, seja em silos tipo bag, ensacados ou em trincheira convencional. Com isso, concentra-se os investimentos em mão-de-obra, maquinário e aquisição de alimentos em uma única época do ano, possibilitando que a operação seja executada na época de safra, quando os preços dos alimentos concentrados normalmente estão mais baixos (DE ÁVILA et al, 2019).…”
Section: Introdução Geralunclassified